Acute effects of aircraft noise on cardiovascular admissions – an interrupted time-series analysis of a six-day closure of London Heathrow Airport caused by volcanic ash. (August 2016) - Pearson, Tim; Campbell, Michael J; Maheswaran, Ravi
Abstract: Acute noise exposure may acutely increase blood pressure but the hypothesis that acute exposure to aircraft noise may trigger cardiovascular events has not been investigated. This study took advantage of a six-day closure of a major airport in April 2010 caused by volcanic ash to examine if there was a decrease in emergency cardiovascular hospital admissions during or immediately after the closure period, using an interrupted daily time-series study design. The population living within the 55 dB(A) noise contour was substantial at 0.7 million. The average daily admission count was 13.9 (SD 4.4). After adjustment for covariates, there was no evidence of a decreased risk of hospital admission from cardiovascular disease during the closure period (relative risk 0.97 (95% CI 0.75–1.26)). Using lags of 1–7 days gave similar results. Further studies are needed to investigate if transient aircraft noise exposure can trigger acute cardiovascular events.